Comment: Businessmen Must Get Active in Politics - Grunewald, Donald (Academy of Management Journal, 1965)
The article explains why businessmen in the United States must become active in politics. The author outlines various talents that businessmen can contribute to the government and reasons behind the relationship between government and business enterprises. An overview of the importance of political action and ways businessmen can be active in politics is provided. A discussion is presented about incentives and methods used by corporations in order to encourage and promote political activity among businessmen.